Efektivitas program pembekalan kemampuan calon guru matematika dalam bidang penilaian - Sarah Inayah (Jurnal Analisa, 2019)
This study aims to develop learning programs and effectiveness in order to improve the ability of prospective mathematics teachers in the field of assessment. This type of research is research and development design (R & D design). This study consists of four stages, namely preliminary studies, program planning, program development and program validation. Preliminary studies were carried out during the initial research activities using various sources in the field and literature review. Program design is done by preparing learning programs in the form of syllabus, Semester Learning Plans , teaching materials, media and evaluation tools. The program that was designed was then developed by means of judgment, trial and revision. From the results of the development then a hypothetical product program is obtained which will be tested for its effectiveness. Effectiveness testing is carried out in program validation activities through the implementation of hypothetical product programs. The results of the study showed that it was effective and efficient in improving the mastery of the theory and practice of evaluating mathematics learning